TRADITIONAL ECOLOGICAL KNOWLEDGE AND ECOSYSTEM SUSTAINABILITY: NEW MEANING TO ASIAN COASTAL PROVERBS - JOHN KURIEN (Ecological Applications, 8(1) Supplement, 1998, pp. S2-S5, 1998)
This article is about the traditional ecological knowledge contained in five proverbs that reveal the wisdom of Asian coastal communities in relation to the coastal ecosystems with which they interact. It attempts to examine these old truths in a search for providing new meanings which may help to obtain stimuli on questions regarding institutions, technology and policy orientation for ecosystem sustainability